DYNAMICS OF FUNCTIONAL LAKE-TO-CHANNEL CONNECTIVITY IN ARCTIC AND BOREAL DELTAS - Dolan, Wayana (University of North Carolina at Chapel Hill Graduate School, 2023)
Lakes in arctic and boreal deltas frequently act as water and sediment traps, delaying the movement of riverine materials to the coastal ocean (coastal deltas) or other waterbodies (inland deltas). The ease with which high sediment water is transported from deltaic distributary channels into deltaic lakes, described as “functional lake-to-channel connectivity,” additionally influences lake biogeochemistry. However, research on lake-to-channel connectivity has either focused on small spatial scales or single instances in time and primarily analyzes structural connectivity (channel presence). Additionally, the impact of functional connectivity on lake biogeochemistry, specifically photochemistry, is poorly constrained. Our research addresses these gaps using remote sensing and field methods to quantify functional lake-to-channel connectivity across dynamic systems and to measure CO2 production via photomineralization in lakes across the connectivity spectrum. In Chapter 1, we investigate functional connectivity in 120 lakes in the Colville Delta (Alaska, United States) at five-year timesteps using Landsat and find that connectivity has remained fairly stable over the past 20 years. Additionally, we detect a correlation between functional connectivity and ice phenology, with connected lake ice starting to break up an average of 26 days earlier than disconnected lake ice. In Chapter 2, we adapt our algorithm to classify functional connectivity in over 10,000 highly dynamic lakes in the Mackenzie Delta (Northwest Territories, Canada) on an image-by-image basis. We find that connected lakes can store 6.9% (1.4 km3) of mean annual flood volume (19.9 km3), 3.7% higher than prior estimates of storage in the Mackenzie Delta. Additionally, we calculate functional sill elevations for 908 lakes, a metric that describes the water level required to move high sediment river water into a lake. Lastly, in Chapter 3, we use a combination of fieldwork, remote sensing, and a model to provide initial constraints on ...